1604 Review of 378 Orchidopexies. (October 2012) - Shoukry, M; Clarke, S; Decaluwe, D; Shamshad, S; Madden, N; Haddad, M; Choudhry, M
Abstract : Background/purpose: To review the outcome of undescended and impalpable testes in terms of atrophic testes at initial operation and complications of atrophy and secondary ascent post orchidopexy. Method: Retrospective review of all orchidopexies carried out between February 2007 and October 2010. Demographic details, age at orchidopexy, operative and postoperative findings were obtained. Findings of testicular atrophy at initial operation, postoperative testicular atrophy and ascent were noted. Results: A total of 378 orchidopexies were carried out in 291 patients in this study period. Only 11% of children underwent orchidopexy at less than one year and 46% at less than 2 years of age. Average follow up period was 20 months (range 1–40). Outcome is shown in tables 1 and 2 . Conclusions: Overall there is higher incidence of atrophic testes noted at initial operation and atrophy post-orchidopexy in impalpable testes. However incidence of these risks is in comparison with the literature in the palpable testes.